POTRET PENGALAMAN PEREMPUAN DALAM CERPEN” SELAMANYA CINTA” KARYA HELVY TIANA ROSA: STUDI EKOFEMINISME TRANSFORMATIF - fitri solihat (IKIP Siliwangi, 2020)
AbstractThis research is based on the writer's reasoning that women have a number of different characteristics compared to men. Women are feeling oriented while men are logic. In a literary work women tend to be portrayed as figures who are gentle, easily oppressed, and resigned to men's feet. The purpose of this study was to find a portrait of women's experiences and analyze their attitudes and struggles in family, social and community life. The research method uses content analysis with qualitative methods. The approach used by the author is transformative ecofeminism based on the theory of Vandana Shiva and Maria Mies with a focus of research on portraits of women's experiences. The research data were obtained from a short story entitled